Strategi Peningkatan Kualitas Kinerja Pendidik di MI Ma’arif Kaliwiro, Kecamatan Kaliwiro, Kabupaten Wonosobo - Sri Nurhayati; Rifqi Muntaqo; Nurul Mubin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to identify strategies for improving the quality of educator performance at MI Ma'arif Kaliwiro, Kaliwiro District, Wonosobo Regency. Focusing on academic and moral aspects as part of the educational vision, this research evaluates the professionalism and effectiveness of the performance of educators at this institution until the 2023/2024 academic year. Qualitative methods are used to collect data through observation, interviews and documentation. The research results show that there are several problems such as lack of discipline, professionalism and effectiveness of teacher performance, which are caused by various factors including leadership, infrastructure and teacher welfare. The proposed strategies include classroom supervision, increasing discipline, motivation, rewards, training, collaboration with other schools, and improving infrastructure. This research emphasizes the need for a comprehensive and sustainable approach to improving the quality of educator performance in order to achieve the expected educational goals..